A Novel Glycosyl Donor with a Triisopropylsilyl Nonparticipating Group in Benzyl-Free Stereoselective 1,2-cis-Galactosylation - Abronina, Polina I.; Zinin, Alexander I.; Malysheva, Nelly N.; Stepanova, Elena V.; Chizhov, Alexander O.; Torgov, Vladimir I.; Kononov, Leonid O. (Synlett, 2017)
A novel glycosyl donor with a triisopropylsilyl (TIPS) nonparticipating group at O-2 is introduced for use in 1,2-cis-galactosylation. Coupling the 2-O-TIPS-substituted thiogalactoside donor with a series of mono- and disaccharide glycosyl acceptors was found to lead exclusively to α-linked oligosaccharides. The observed exceptionally high α-selectivity was interpreted in terms of conformational changes in the glycosyl cation induced by the bulky 2-O-TIPS group.
Keywords: glycosylation; stereoselectivity; stereoselective synthesis; conformation; protecting groups; triisopropylsilyl group; 4-(3-chloropropoxy)phenyl glycosides